The Improvement of Product Quality and Increase in Production Quantity through the Implementation of Apec_3 (Ecoprint Steaming Tool) at the Ecoprint Msme 'Citra Collection' in Tegal City - Hidayat , Tofik; Budiyanto, Andi; Florina, Ike Desi; Musyassaroh, Inas Sany; Nindya, Meyga Agustia (ASEAN Journal of Empowering Community, 2024)
Citra Collection MSME is a business engaged in the production of ecoprint fabric. This MSME was established in 2017 by Retno Wulansari. It produces clothes, bags, shoes, and wedding or seminar accessories using fabrics and leather that have been ecoprinted. The demand for ecoprint fabric products is very good, and sales volume has increased. However, some consumers are particular about the ecoprint results, particularly the quality issues, such as wrinkles and color fading. The company also faces difficulties in increasing its boiling capacity due to the limited design of its equipment. So far, the company has been using a meatball pot (manci bakso) for the ecoprint boiling process. Seeing these issues, this community service aims to help improve the quality of ecoprint products and enhance the production process. The method used in this community service is the Participatory Action Research (PAR) method. The PAR method involves the business or MSME from the start, with the hope of delivering targeted and effective results. By implementing APEc_3, the company is able to increase production capacity. This tool can process 30 pieces of fabric in one boiling session. The use of a roll made from stainless steel material helps eliminate wrinkles and prevent color fading, which has always been a problem with the 'manci bakso' equipment.